A cooperação entre a União Europeia e Cabo Verde nos anos 90. Cooperação bilateral e multilateral com a ilha de Sto. Antão: A importância de planos integrados - Maria Manuela Cardoso (Cadernos de Estudos Africanos)
Taking as a starting point the fact that Cape Verde is one of the countries whose viability and development depend to a large extent on foreign aid, this article analyses the impact of European development cooperation on the island of Santo Antão. The results presented are entirely positive, with regard to the creation of (material and organizational) infrastructures as well as with regard to the mobilisation of local social actors.